Analisis Pengaruh Pendidikan dan Gini Rasio terhadap Tingkat Pengangguran di Kalimantan Selatan - Anwar , Kasypul (Penerbit Goodwood, 2023)
Purpose: The unemployment rate as well as the labor force indicate the large number of people who must be included in the development process. This shows that the dynamics of the development process must be able to involve the entire work force, meaning that a large number of work force can become a burden for economic development. Apart from education, another aspect that influences the unemployment rate is the unequal distribution of income (gini ratio). Inequality in income distribution is a problem of differences in income between the richest and the poorest individuals. The greater the income gap, the greater the variation in income distribution. This study aims to obtain quantitative